PENGGUNAAN METODE MUROJA’AH PADA HAPALAN SURAH PENDEK DI TK ISLAM SULTONIYAH SAMBAS TAHUN AJARAN 2023-2024 - uliyani, Uliyani; Dewi ferawati; Sera Yuliantini (Samawa (Sakinah, Mawaddah Warahmah), 2025)
This research aims to describe and analyze the following: 1) The preparation for implementing the muroja’ah method on short surah memorization; 2) The implementation of the muroja’ah method on short surah memorization; and 3) The results of the muroja’ah method implementation at TK Islam Sultoniyah Sambas during the 2023-2024 academic year. This study uses a qualitative approach with a phenomenological research type. Data collection techniques employed include observation, interviews, and documentation. The data analysis techniques used are data collection, data reduction, data display, and conclusion drawing. The data validity techniques used are triangulation and member checking. The research findings conclude that: 1). The preparation for implementing the muroja’ah method on short surah memorization at TK Islam Sultoniyah Sambas during the 2023-2024 academic year involves: preparing the mutaba’ah book (monitoring log) and determining the short surahs to be memorized. 2). The implementation of the muroja’ah method on short surah memorization at TK Islam Sultoniyah Sambas during the 2023-2024 academic year proceeds as follows: the teacher prepares the students for lining up, then the teacher prepares students for line-up activities such as singing, clapping, and reciting the short surahs previously memorized. After that, the children are prepared to enter the classroom. The teacher prepares the attendance activity while singing, recites prayers, and conducts the Dhuha prayer activity. After the prayer, the children submit their memorization that they have practiced at home. 3). The result of the muroja’ah method implementation on short surah memorization at TK Islam Sultoniyah Sambas during the 2023-2024 academic year is: the children's memorization significantly improves through the muroja’ah method.